Gestión pública y su relación con el impuesto predial en la Municipalidad Distrital de Punchana, periodo 2023 - Paredes Freyre, Diana Carolina (2025)
The objective of this research was to determine how public management is related to the property tax in the District Municipality of Punchana during the period 2023, with a quantitative research approach of non-experimental design and type of transversal design of correlational scope, I include as population to 32 public servants who work in the Municipality of Punchana in addition to records that allow us to identify the collection obtained by the municipality in the period 2023, the investigation concluded that the high significant positive correlation between Public Management and Property Tax (ρ = 0.890) indicates a close relationship between effectiveness in public management and property tax management. This suggests that improvements in public management, such as the implementation of efficient policies, better administration and adequate monitoring of tax obligations, are strongly associated with better property tax management.